(untitled) (Pedagogy of Higher and Secondary Education, 2004)
About the new approaches to using the mathematical tasks as the didactical means of training, development and education of younger schoolchildren. There is on the grounds of conceptual object the mathematical education opens the importance of construction approaching in educational the mathematic in this article. Author proposes to use the mathematical tasks, their didactical functions with object to form the definite creation knowledges the younger schoolchildren.